Epidemiological aspects of scrotal and testicle trauma in modern metropolis - S. K. Yarovoy; R. A. Khromov; Sh. L. Voskanyan (Исследования и практика в медицине)
The article analyzes the data of 414 patients with scrotal and testicular injuries treated in 2008–2017 by the forces of urgent andrologic service in Moscow.More than 90% of patients who applied for injury to the scrotum and testicle were under the age of 60 years. In peacetime, in the conditions of the metropolis (Moscow) in the vast majority of cases there is a blunt (without breaking the integrity of the skin) injury of the scrotum and testicle (a total of 89.4%). Of these, 77.3% are blunt sports and domestic injury of the testicle of varying severity with a pronounced predominance of relatively light injuries, in particular, the bruise of the testicle. Open injuries are relatively rare-a total of 10.6%. Among open injuries, ruptures of the scrotum without damage to its organs are predominate (63.6% of the total number of patients who applied for open wounds of the scrotum and its organs).The need for emergency surgical interventions in scrotal injury was unexpectedly low-53.1%, which is due to the predominance of mild trauma options – scrotal injury and testicular injury (a total of 61.4% in the frequency of urological care), in certain situations allowing the possibility of conservative treatment or even dynamic observation.